Collaborative Governance Between the UPT DP3AP2KB, Health Services, and Village Government in Reducing Stunting Prevalence in Sape District - Junaidin; Arman; Muhammad Nur; Firmansyah (KOMUNITAS, 2025)
This study analyzes the effectiveness of collaborative governance implemented by UPT DP3AP2KB in partnership with health services and village governments to accelerate stunting reduction in Sape District, Bima Regency. Using a descriptive qualitative case study, data were obtained through interviews, observation, and document analysis with village officials, UPT staff, health workers, and posyandu cadres. The findings indicate that cross-sector collaboration operates through institutional arrangements such as the Stunting Reduction Acceleration Team and village forums, supported by facilitative leadership in aligning stakeholder interests. Collaborative processes rely on communication, trust, shared commitment, and common goals. The collaboration has improved targeted interventions, particularly maternal and child nutrition programs, although challenges persist, including limited nutritional literacy, inadequate technical personnel, and weak intersectoral data integration. The study recommends strengthening village capacity, improving data coordination mechanisms, and expanding collaborative networks to ensure sustainable and effective governance.